Analisis Peranan Guru Mata Pelajaan Aqidah dalam Menanamkan Nilai Keagamaan - M Masrur Huda; Moh Ismail (EDUCATIO : Journal of Education, 2017)
The purpose of the study is to know the role of Guru Aqidah Akhlak in embedding the value of Aqidah. The research methods used are included in qualitative research. In data collection, researchers use observation methods, in-depth interviews and documentation. As for its analysis, researchers use qualitative descriptive analysis techniques, namely data reduction, data presentation and verification. This research also checks the validity of data with triangulation, observation provisions and peer discussion. For the research, phase uses the preparation stage, fieldwork stage, and completion stage. The results of the study showed that teachers of the teacher's creed in instilling the value of faith in the students, which is the teacher in the role of conducting and motivator to students, besides the teachers also perform religious habituation in the field of creed such as praying set IAP before and after learning is completed, reading Yasin letters and verses Al-Qur ‟ An, read Asmaul Husna, and memorized short letters, and teachers also held extra activities BTQ and calligraphy.